X‐ray Diffraction Study of the Effect of High‐Temperature Heat Treatment on the Microstructural Stability of Third‐Generation SiC Fibers. Issue 5 (28th February 2013) - Gosset, Dominique; Colin, Christian; Jankowiak, Aurelien; Vandenberghe, Thierry; Lochet, Nicolas; Hay, R.
<x xml:space="preserve">Abstract</x> Third‐generation SiC fibers [High Nicalon S (HNS) and Tyranno SA3 (Ty–SA3)] were studied by X‐ray diffraction and transmission electron microscopy (TEM) after heat treatments in neutral atmosphere up to 1900°C. The microstructural changes in both materials were determined using a modified Hall–Williamson method introducing an anisotropy parameter taking into account the high density of planar defects. HNS fibers exhibit significant modifications in the coherent diffraction domains (CDD) size, which drastically increases from 24 to 70 nm in the range 1600°C–1900°C. TEM observations support these results. The residual microstrain values decrease from 0.0015 to 0.0005 between 1750°C and 1850°C. Similarly, the anisotropy parameter significantly decreases in the same temperature range. Concerning the Ty–SA3 fibers, no evolution in terms of CDD size and residual microstrain was observed. However, the anisotropy parameter decreases at 1800°C. TEM observations did not show noticeable grain growth. The grain size was found to be larger than the CDD and the planar defects density to decrease at high temperature. In both types of fibers, the CDD sizes are similar for the highest temperature heat treatments.